ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTATION IN PEDIATRIC MYELODYSPLASTIC SYNDROMES: A SINGLE CENTER EXPERIENCE FROM TURKEY - Atay, D.; Erbey, F.; Akcay, A.; Ozturk, G. (FERRATA STORTI FOUNDATION, 2017)
22nd Congress of the European-Hematology-Association, Madrid, SPAIN, JUN 22-25, 2017